2021
DOI: 10.1002/cben.202100028
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Fermentation Processes: Modes of Operation and Application

Abstract: Bioprocesses can be hampered by product concentrations within a fermentation leading to product‐inhibition, and reductions in yield and productivity. This limitation impacts operational considerations, process economics, and viability, and, ultimately, whether a technology is industrially viable. One approach to circumventing these concerns is in situ extraction of products. In this way, the organism is no longer exposed to the inhibitory product, and fermentation can proceed, often at improved rates. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…Inspired by the above results about the higher reaction rates with furfural (Figure C), it is envisioned that the catalytic efficiencies of whole cells may be greatly increased by improving mass transfer (e.g., increasing cell membrane permeability). In extractive fermentation, hydrophobic solvents are usually added to improve the cell membrane permeability as well as to in situ recover products . Considering the fact that acetate esters are used as acyl donors in the following BHMF diacetate synthesis, the intensification of biocatalytic BHMF synthesis was performed by using acetate esters (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the above results about the higher reaction rates with furfural (Figure C), it is envisioned that the catalytic efficiencies of whole cells may be greatly increased by improving mass transfer (e.g., increasing cell membrane permeability). In extractive fermentation, hydrophobic solvents are usually added to improve the cell membrane permeability as well as to in situ recover products . Considering the fact that acetate esters are used as acyl donors in the following BHMF diacetate synthesis, the intensification of biocatalytic BHMF synthesis was performed by using acetate esters (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In extractive fermentation, hydrophobic solvents are usually added to improve the cell membrane permeability as well as to in situ recover products. 64 Considering the fact that acetate esters are used as acyl donors in the following BHMF diacetate synthesis, the intensification of biocatalytic BHMF synthesis was performed by using acetate esters (Figure 3). Figure 3A shows the effect of EtOAc contents on the HMF reduction.…”
Section: Table 1 Apparent Kinetic Parameters Of Adhs Toward Hmf and N...mentioning
confidence: 99%
“…A study by (Nascimento et al, 2023) methods can be challenging due to the interference of biomass with downstream separation processes-biomass will also be collected along with precipitated MELs. Consequently, additional cell separation techniques may be required before implementing an in situ precipitation process (Teke, Tai, et al, 2022). In the context of the study by Kitamoto, Akiba, et al (1990), observed coprecipitation of MELs with yeast cells and oil at reduced pH levels may be linked to their association with other components like proteins, oil, and FFA in the fermentation broth, rather than a direct response to pH changes.…”
Section: Membrane Filtrationmentioning
confidence: 99%
“…Due to product toxicity and possible product degradation, VFA extraction steps were strategized to selectively recover (and potentially concentrate) the targeted VFAs and achieve simultaneous impurity and contaminant removal. Numerous methods have been employed to extract VFAs from the aqueous phase, including electrodialysis, adsorption, and liquid-liquid extraction (LLE) [32]. It is noted that the extraction steps are often followed by a secondary purification stage, using technologies including distillation, evaporation, and crystallization, to reach the targeted purity for potential sale in the market or downstream upgrading [33].…”
Section: Extraction Of Vfasmentioning
confidence: 99%
“…The liquid used as the extracting solvent is commonly called the extractant, while the other liquid phase is known as the raffinate. During LLE, VFAs are partitioned from the digestate (raffinate phase) to the solvent phase, and the partition coefficient relies on multiple factors, such as digestate pH, initial VFA concentration, and any other solutes in the digestate [32]. However, solvent selection is particularly important for extraction performance.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%